The Relationship Effect of Organizational Climate In between Strategic leadership and Organizational Innovation at Private Hospitals in Amman - Agrizat, Ahmad; Megdadi, Younes (International Review of Management and Marketing, 2025)
This research aimed to identify the relationship effect of organizational climate role between strategic leadership and organizational innovation in Jordanian private hospitals. A quantitative and descriptive analytical approach was employed, with the research population consisting of hospitals with more than 50 beds, totaling 29 out of 48 hospitals. The sample was selected using a stratified sampling method, comprising hospital workers, specifically managers and heads of departments in middle management, with a total of 432 individuals (170 managers and 262 department heads). Data were collected from the research sample through an electronically distributed survey. The statistical analysis of the hypotheses was conducted using SPSS. The research findings reveal a statistical significant effect of strategic leadership on organizational innovation, and a statistical significant effect of strategic leadership on organizational climate as a mediating variable, and a statistical significant effect of organizational climate on organizational innovation. Additionally, a partial significant relationship of organizational climate between strategic leadership and organizational innovation. Both theoretical and practical contributions were provided to assist and guide private hospital administrations in enhancing innovative environment to creative thinking and initiative. The research recommends private hospitals administration to organize workshops and training courses to enhance employees creative thinking to enhance organizational creativity skills of leaders within private hospitals.